PENERAPAN SANKSI TERHADAP ANAK PELAKU TINDAK PIDANA NARKOTIKA DI PENGADILAN NEGERI PEKANBARU - RANA SAPUTRA; Firdaus '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The National Law Agency states that in the UK there has been a long history, the king has a prerogrative right to act as a parat paatariae is to protect the people who need help including children who need help, while children who commit crimes are not punished but must be protected and given assistance . Child protection came into existence by the early establishment of the Juvenile Court of 1889 at Minos Ilinois United States. Child protection is implemented in a rational, responsible and beneficial way of representing an effective and efficient business. Child protection efforts can not lead to the death of initiatives, creativity, and other things that lead to dependence on others and uncontrollable behavior, so children do not have the ability and willingness to exercise their rights and carry out their obligations. If they mature their physical and mental and social growth then their words will replace the previous generation. In Law Number 35 Year 2009 regarding Narcotics, there is no specific explanation in the criminal lawsuit against the offenders of Narcotics. Only arrangements about mandatory reporting for parents or carers from Narcotics addicts who are not old enough and the addict themselves to the public health center, the hospital, and / or medical and social rehabilitation institutions. Based on this understanding, this writing sums up three problems, Firstly, the implementation of criminal sanctions against children of narcotics offenders in Pekanbaru State Second Court, Second, Judgment in which the judge uses in determining criminal sanctions against children of narcotics offenders in the District Court of Pekanabaru the verdict has been in accordance with the Laws and Regulations.This type of research can be classified in Normative research type, because the research method used is Normative research method, that is method which researcher to discuss about legal principles, legal system, legal synchronization level, legal history and legal protection.From the research results of the problem there are three main things that can be concluded, First Implementation of criminal sanctions against the perpetrators of narcotics abuse in the area of Pekanbaru District Court should be adjusted to the applicable legislation and basically aims to provide psychological effects or deterrent to the narcotics users that the user No longer use narcotics after completing the sentence handed down by the judge. The second consideration of the judge in the application of criminal sanctions against the child of the perpetrators of narcotics crime in the Pekanbaru District Court is that the child who performs the delinquency of the handling and the settlement should be wisely and as far as possible from the intervention of the judicial system without neglecting law enforcement and justice in order to ensure that The settlement is done solely for the welfare of the child concerned and the public interest of the child who performs the delinquency and the perpetrator of the crime or the victim of narcotics addiction to the children who will be sentenced to their criminal must also be given treatment and care Author's suggestion Implementation of criminal sanctions against the child The perpetrators of Narcotics crime in the Pekanbaru District Court The application of criminal sanctions against narcotics abusers is basically aimed at giving psychological effect or deterrent to the narcotics user so that the user no longer use The narcotics after completing the sentence imposed by the judge.Keywords: Implementation Of Sanction - Child Crime - Narcotics